Ethanol extracts of Danlou tablet attenuate atherosclerosis via inhibiting inflammation and promoting lipid effluent. (August 2019) - Hao, Deng; Danbin, Wu; Maojuan, Guo; Chun, Sun; Bin, Lu; Lin, Yang; Yingxin, Sun; Guanwei, Fan; Yefei, Chen; Qing, Gao; Xijuan, Jiang
Graphical abstract: Abstract: As a chronic inflammatory disease, atherosclerosis is characterized by accumulation of lipid-rich macrophages on the inner walls of arteries. Deposited macrophages promote atherosclerotic lesion progression; therefore they are viewed as the main targets in order to alleviate atherosclerosis. Danlou tablet, a patented Chinese Medicine, has long been used to treat cardiovascular diseases. In the present study, we used Apolipoprotein E-deficient (ApoE −/− ) mice model and in vitro cell line of RAW264.7 to explore the mechanisms of ethanol extracts of Danlou tablet (EEDT) in treating atherosclerosis. The potential targets that EEDT works to treat atherosclerosis were predicted by "Network pharmacology analysis", based on which we designed mRNA array of 93 genes. Then mRNA array and oil red O staining were performed in aortic extracted from the cohorts of Control (C57BL/6 mice, chow fed), Model (ApoE -/- C57BL/6 mice, 20 weeks of high-fat diet) and EEDT intervening (ApoE -/- mice, 20 weeks of high-fat diet with 12 weeks of EEDT treatment) group. Furthermore, mRNA array, inflammation cytokines and lipid content were examined in RAW264.7 cell line. It was showed that EEDT decreased the expressions of inflammation cytokines by down regulating NF-κB singling pathway and accelerated cholesterol effluent through activating PPARα/ABCA1 signaling pathway. On the other hand, activation of NF-κB pathway or suppression of PPARα/ABCA1 signaling pathway both abolished the therapeutic effect of EEDT. In conclusion, EEDT played a key role in anti-inflammation and preventing lipid deposition in macrophages of atherosclerosis via suppressing NF-κB signaling and triggering PPARα/ABCA1 signaling pathway.